The impact of internet use on physical activity among Chinese older adults: the mediating role of social support - Yifei Shen; Yifei Shen; Chuntian Lu; Bin Wang (Frontiers in Public Health)
BackgroundThe positive impact of Internet use on enhancing physical activity among older adults is an important response to the aging problem in the new era. However, while previous studies have explored the important impact of Internet use on physical activity among older adults, the specific mechanisms of this impact have not been much analyzed. In an attempt to answer this question, we further focus on the mediating role of social support in the relationship between Internet use and physical activity among older adults.MethodsThis study utilizes data from the 2021 China General Social Survey (CGSS) to categorize social support into three dimensions: support from relatives, friends, and neighbors. A nested multiple OLS regression model is employed to analyze the impact of internet use on physical exercise among the old adults. Additionally, the SPSS macro PROCESS is used to test the mediation effect, examining the mediating role of social support in this relationship.ResultOur research findings indicate the following: (1) Internet use significantly and positively predicts physical exercise among the old adults; (2) Social support exerts a positive influence on physical exercise in this population; and (3) Social support partially mediates the relationship between internet use and physical exercise among the old adults.ConclusionThe study concludes that increasing Internet penetration among the old adults is of great practical significance in expanding their social support network and promoting physical activity. The results of the study provide new perspectives on the layout of work on ageing and policies for healthy ageing in the new era, as well as lessons for other developing countries on the issue of ageing.